Effect of time between adhesive application and photoactivation on adhesion and collagen exposure - Salles Scheffel, Debora Lopes [UNESP]; Estrela, Renata Pereira [UNESP]; Pires, Paula Maciel [UNESP]; Mariusso, Matheus Racy [UNESP]; Souza Costa, Carlos Alberto de [UNESP]; Hebling, Josimeri [UNESP] (Mosher & Linder, Inc, 2014)
Purpose: To evaluate the influence of the time elapsed between the application and photoactivation of Single Bond 2 (SB) on microtensile bond strength (mu TBS) and collagen exposure at the adhesive interface produced in the presence of intrapulp pressure. Methods: Dentin occlusal surfaces were prepared in 72 molars, and divided into eight groups (n= 9). After acid etching, SB was applied, with or without simulated intrapulp pressure, and remained undisturbed for 0, 20, 40 or 60 seconds, before photoactivation. Three teeth/group were processed for staining with Goldner trichrome and evaluation of the thickness of exposed collagen zone (CZ) at the base of the hybrid layer. Composite resin build-ups were placed on the remaining six prepared teeth prior to sectioning for microtensile testing. Data were submitted to ANOVA and Tukey tests (alpha= 0.05). Results: In the absence of pressure, immediate photoactivation resulted in the lowest mu TBS, while the other groups did not differ among them. Under intrapulp pressure, the lowest values were observed after 60 seconds. There was no difference in the thickness of the exposed collagen zone among the groups without pressure. However, thicker layers were recorded in the presence of pressure after 40 and 60 seconds. Waiting 60 seconds between application and photoactivation of SB significantly reduced resin-dentin bond strength when pulpal pressure was simulated.